TRANSIDIOMATIC PRACTICES IN A DEAF-HEARING SCENARIO AND LANGUAGE IDEOLOGIES - Cavalcanti, Marilda C.; Silva, Ivani Rodrigues (Revista da Anpoll, 2016)
With a focus on deaf-hearing interaction, the aim of this paper is to reflect on what happens when misunderstandings in communication occur. The scenario for the interaction is a reading workshop carried out as part of an educational project. The issue for investigation arose in the reading of the transcriptions of the video data generated in the fieldwork of an ethnographic project. Our presupposition is that this type of interaction is multilingual and that this multilingualism is more complex and comprehensive than the use of separate languages. The data analysis is theoretically informed by the concept of transidiomatic practices against the background of language ideologies. This work is licensed under a Creative Commons Attribution 3.0 License.